What is the most dangerous sexual position that caused the penile fracture? A systematic review and meta-analysis - Syarif Syarif; Abdul Azis; Ahmad Shafwan Natsir; Muhammad Zulharyahya Dandy Asmara Putra (International Brazilian Journal of Urology, 2024)
ABSTRACT Purpose: Penile fracture (PF) affects 1,14 to 10,48 men in every 100.000 men in East Asia, and the primary aetiology is sexual intercourse, but the knowledge regarding the most dangerous sexual position is not well explained. This study compares three sexual positions: man on top position (MTP), woman on top position (WTP), and doggy style position (DSP), leading to PF potential. Materials and methods: A search of sexual position-related PF in Google Scholar, PubMed, Cochrane, and PMC Europe was performed. Criteria inclusion was the full text of relevant articles which describ the number of sexual positions. It was analyzed by odds ratio, random model effect, and the OR and 95%CI were calculated. Results: Twelve relevant papers involving 490 patients comprised 169 MTP, 120 WTP, 158 DSP, and 43 no intercourse cases. Meta-analysis of all sexual positions was a MTP P= 0,04, WTP P=0,49, and DSP P=0,0005. Conclusions: The man-dominant positions (MTP and DSP) were significantly potential for PF, which speculated that when a man is dominant and very excited, intercourse may become highly vigorous and impact trauma. This study found that man's dominant position consists of DSP and the MTP significantly lead to PF.